(untitled) (Tempo e Argumento, 2021)
It is not easy to address the Brazilian military dictatorship in History classes. Teachers need to rely on official documents legitimizing the approach to this theme and Education in Human Rights. Also, we need to know clearly what we would like our students to learn, given the mistaken ideas that exist today about the dictatorship and the transition to democracy. Bringing memory disputes into the classroom may be promising. And, working with documents, seek to understand people’s actions during that period, not emphasizing ‘ethical lessons,’ but the understanding of historicity. Thus, perhaps we can perhaps provide effective learning, which allows for a re-ordering of knowings, considering the complexity of the past and present. Keywords: History teaching. Military dictatorship. Memory disputes. Working with documents.